An Integration of Open-Source Resources in Distance Teaching for Real-Time Embedded System Using Arduino Microcontroller and Freertos - Chia, Kim Seng (International Journal of Integrated Engineering, 2022)
Real-Time Embedded System (RTES) is about applying real-time system in an embedded system (e.g. microcontroller) in ways that both logical and temporal requirements are fulfilled. A special attention shall be on the temporal response analysis so that students can have a clear distinction between microcontrollers with and without real-time system. During new norms of learning and teaching from home, an affordable and accessible infrastructure in RTES course is urgently needed. Thus, this study aims to evaluate the feasibility of an integration of open source resources (i.e. Arduino platform and FreeRTOS) in teaching RTES remotely and to provide real-time learning experience about RTES concepts without additional components or wiring out of school. Results show that an obvious context switch could be observed when task pre-emption happened. Finding indicates that the proposed integration was useful for students to understand the complex RTES concepts e.g. task scheduling, pre-emption, and mutually exclusion.